Ability of two new thiazolidinediones to downregulate proinflammatory cytokines in peripheral blood mononuclear cells from children with asthma - Moacyr Jesus Barreto de Melo Rêgo; Adriana Azoubel-Antunes; Mariana Brayner-Cavalcanti Freire Bezerra; Michelly Cristiny Pereira; Juliana Cruz da Silva; Thiago Ubiratan Lins e Lins; Emanuel Sávio Cavalcanti Sarinho; Cézar Augusto da Cruz Amorim; Maria do Carmo Alves de Lima; Marina Rocha Galdino-Pitta; Ivan da Rocha Pitta; Maira Galdino da Rocha Pitta (Universidade de São Paulo, 2018)
Allergic asthma is a chronic, complex inflammatory disease of the airway. Despite extensive studies on the immunomodulation of T helper (Th) cell pathways (i.e., Th1 and Th2) in asthma, little is known about the effects of Th17 pathway modulation, particularly that involving peroxisome proliferator-activated receptors (PPARs). In response, two new thiazolidinedione derivatives-namely, LPSF-GQ-147 and LPSF-CR-35 were synthesized and evaluated for their immunomodulatory effects on Th17-related cytokines, including interferon γ (IFNγ), interleukin IL-6, IL-17, and IL-22 in the peripheral blood mononuclear cells of asthmatic children. Both compounds were nontoxic even at high concentrations (i.e., 100 µM). The LPSF-CR-35 compound significantly reduced the levels of IL-17A (p = .039) and IFNγ (p = .032) at 10 µM. For IL-22 and IL-6, significant reduction occurred at 100 µM (p = .039 and p = .02, respectively). Conversely, LPSF-GQ-147 did not significantly inhibit the production of the tested cytokines, the levels of all of which were more efficiently reduced by LPSF-CR-35 than methylprednisolone, the standard compound. Real-time polymerase chain reaction assay confirmed that LPSF-GQ-147 has significant PPARγ modulatory activity. Such data indicate that both LPSF-CR-35 and LPSF-GQ-147 are promising candidates as drugs for treating inflammation and asthma.